Chromium removal from aqueous solution by the ferrite process - Erdem, Mehmet; Tümen, Fikret (My University, 2004)
This research summarises the results of the study on the removal of chromium by applying the ferrite process to the solutions obtained from two different Cr(VI) reduction processes utilising sodium sulphite and ferrous sulphate as reducing agents. For both solutions containing trivalent chromium ions, the optimum treatment conditions were determined. The generated sludges were characterised by XRD analysis and physical tests. In addition, to explore the dissolution properties of the sludges obtained, they were contacted with the solutions of sulphuric, citric, tartaric, oxalic and ascorbic acids and EDTA. Also, the sludge samples were subjected to standard toxicity characterisation leaching procedure (TCLP) test of USEPA in order to determine the pollution potential. An efficient Cr(III) removal (about 100%) in the solution from the Cr(VI) reduction process utilising sodium sulphite as reducing agent was achieved when the solution was treated at pH 9 and 50 °C for 60 min in the presence of Fe2+/Cr3+ weight ratio of 16. For the other Cr(III) solution prepared from Cr(VI) reduction by ferrous sulphate, a Fe2+/Cr3+ weight ratio of 17.9 at the same conditions was found to produce complete removal of Cr(III). It was determined that the spynel chromium–iron compounds obtained in the process were in the form of chromite (Cr2FeO4). Dissolution experiments and TCLP tests show that the concentrations of the chromium dissolved from both sludges were below the limit given as 5 mg l?1 by USEPA. The results showed that Cr(III) removal through ferrite process provides the advantages that the sludges generated are non-voluminous, easily separable and environmentally stable.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Wastewater treatment; Chromium removal; Ferrite process; Dissolution; TCLP